Experience of Cyberbullying among Nursing Students - Bharati, Mamata; Dhakal Chalise, Gita; Bhandari, Sunita; Gautam, Puspa; KC, Ambu; Regmi, Kalpana; Adhikari, Bibhav (Journal of Karnali Academy of Health Sciences, 2021)
Background: Cyberbullying is a form of bullying or harassment repeatedly with intent to harm others by using internet and electronic devices mainly from social media sites. It is a burning issue among the students of school and university level and affecting their psychosocial health and academic performances considerably. Therefore, this study was conducted to identify the cyberbullying experience among nursing students.Methods: Descriptive cross–sectional study design was used in this study. Ethical approval was obtained from Institutional Review Committee of Nepalese Army institute of Health Sciences (IRC, NAIHS). Permission for data collection was obtained from the principal of the Norvic Institute of Nursing Education and informed written consent was taken from each participant. Census method was used in the study, out of total (360) students 213 students participated in this study. Data was collected using self–administered, semi– structured questionnaire through online google form. Data was analyzed using descriptive statistics in SPSS 16.Results: In this study, more than one third (34.7%) of the participants experienced cyberbullying during last one year and highest proportion (44.6%) of them bullied through repeated harmful/teasing/threatening text messages. Most (70.3%) of the participants faced problems from the cyberbullying; among them, 61.5% participants faced academic problems, 57.7% faced psychological problems and 48.1% faced social problems.Conclusions: Based on the study findings, cyberbullying experiences was common problem among the nursing students and most of them suffered from academic, psychological and social problems. Therefore, it is important to aware the students and their parents about rational use of internet, cyber bulling and its impact in health and academic achievement.